The Indian family in transition : reading literary and cultural texts - Dasgupta, Sanjukta; Lal, Malashri (SAGE Publications, 2007)
This book critiques literary and cultural representations of the Indian family to explore the manner in which the family and its structure are in transition. The various papers explore (and expose) how the Indian family, whether in India or abroad, needs to be redefined in the current context--in this age of rapid industrialization, globalization (both cultural and economic) and the emergence of new technologies. The family is viewed from a variety of perspectives, as represented in film, theatre and literature--both in English and in the vernacular. Including reflective pieces by several well-k.